The Organization of the Innovation Industry: Entrepreneurs, Venture Capitalists, and Oligopolists - Pehr-Johan Norbäck; Lars Persson (The Research Institute of Industrial Economics (IUI), 2004)
The starting point of this paper is that the exit of venture-backed firms often takes place through sales to large incumbent firms. We show that in such an environment, venture-backed firms have a stronger incentive to develop basic innovations into commercialized innovations than incumbent firms, due to strategic product market effects. In turn, this will increase the price for basic innovations, thereby triggering more basic innovations by entrepreneurs. Consequently, the presence of a venture capital market implies that more basic innovations are created and that these become better developed.
Keywords: G24; L10; L20; M13; O30; 330; Acquisitions; Entrepreneurship; Innovation; Venture Capital; Innovation; Risikokapital; Entrepreneurship-Ansatz; Oligopol; Übernahme; Theorie